Recommendations and strategies for evaluating in higher education: proposal for an evaluation model focused on learning - Solórzano Vargas, William (2023)
This document presents a proposal for an evaluation model oriented to the learning of students. The fundamental objective is to provide inputs that are of practical use to university teaching staff, with the aim of contributing to improving the complex work of evaluation. educational. It is aimed at higher education teachers of all academic disciplines; In it you can find a set of guiding principles for a type of evaluation that encourages the development of skills and promotes the acquisition of significant learning in students, as opposed to the mere measurement and qualification of knowledge. This model was developed from the review of existing literature and is nourished by the knowledge generated in research, through interviews applied to a group of teachers from the Western Headquarters, of the University of Costa Rica; who generously shared experiences that have been successful in evaluation matters. Equally valuable for the construction of this evaluative proposal have been the contributions and suggestions of the third and fourth year students of the Baccalaureate in the Teaching of Mathematics and the Baccalaureate in the Teaching of Social Studies and Civics, from the Headquarters of West. Especially with regard to the evaluation strategies that they consider most useful for achieving significant learning and for strengthening fundamental skills in their professional and personal development.